2018
DOI: 10.1111/jcmm.13897
|View full text |Cite|
|
Sign up to set email alerts
|

Therapeutic effects of lentinan on inflammatory bowel disease and colitis‐associated cancer

Abstract: In this study, we investigated the therapeutic potential of lentinan in mouse models of inflammatory bowel disease (IBD) and colitis‐associated cancer (CAC). Lentinan decreased the disease activity index and macroscopic and microscopic colon tissue damage in dextran sulphate sodium (DSS)‐induced or TNBS‐induced models of colitis. High‐dose lentinan was more effective than salicylazosulfapyridine in the mouse models of colitis. Lentinan decreased the number of tumours, inflammatory cell infiltration, atypical h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 59 publications
0
37
0
Order By: Relevance
“… 18 , 19 Furthermore, other reports have indicated that LNT can shift the cytokine activities of T helper (Th) cells toward Th1 cells by altering the equilibrium between reductive and oxidative macrophages. 20 Therefore, it is reasonable to propose that in this bladder cancer model, LNT initially induced macrophage activation, then enhanced the proliferation of CD4 + and CD8 + T cells, and finally upregulated the expression of IFN-γ and IL-2. 21 , 22 Meanwhile, the percentages of MDSCs and Tregs were downregulated, leading to a reduction of the anti-inflammatory cytokines IL-10 and TGF-β.…”
Section: Discussionmentioning
confidence: 87%
“… 18 , 19 Furthermore, other reports have indicated that LNT can shift the cytokine activities of T helper (Th) cells toward Th1 cells by altering the equilibrium between reductive and oxidative macrophages. 20 Therefore, it is reasonable to propose that in this bladder cancer model, LNT initially induced macrophage activation, then enhanced the proliferation of CD4 + and CD8 + T cells, and finally upregulated the expression of IFN-γ and IL-2. 21 , 22 Meanwhile, the percentages of MDSCs and Tregs were downregulated, leading to a reduction of the anti-inflammatory cytokines IL-10 and TGF-β.…”
Section: Discussionmentioning
confidence: 87%
“…Although a large number of studies have proposed treatments for this disease, a safe and therapeutic strategy is still urgently needed. Lentinan, a polysaccharide derived from Lentinus edodes, has shown protective properties in inflammatory skin diseases, 26 inflammatory bowel disease, 27 and different cancers. 28 In the present study, we employed lentinan to antagonize inflammation induced by AGEs in human chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Lentinan was purchased from Kaifeng Pharmaceutical Co. (Henan, China) 22 as powder in a penicillin bottle. Lentinan was dissolved in PBS right before use.…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Lentinan (LNT) is a special type of β-glucan obtained from Lentinus edode and has a wide variety of biological and physiological activities 13 . LNT is used in clinics for the treatment of malignant ascites in China, which has high security but low efficiency 14 , 15 . Selenium (Se) has a potential application in cancer therapy due to its excellent biological activity and low toxicity 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%